2012
DOI: 10.1089/gtmb.2011.0045
|View full text |Cite
|
Sign up to set email alerts
|

Professional Perspectives About Pharmacogenetic Testing and Managing Ancillary Findings

Abstract: Aims: Pharmacogenetic (PGx) tests, intended to inform therapeutic decision making through prediction of patient likelihood to respond to or experience an adverse effect from a specific treatment, may also generate ancillary, or incidental, disease information unrelated to the purpose for which the test was ordered. To assess attitudes toward PGx testing, ancillary disease risk information, and related clinical issues, we conducted a series of focus groups among health professionals. Results: Twenty-one primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 22 publications
3
60
0
Order By: Relevance
“…It is known that initial strong interest in genetic testing does not always translate into actual uptake of testing Meiser and Dunn 2000); thus the major weakness of this study, shared with almost all studies published in this area (Biesecker et al 2009;Bloss et al 2010;Facio et al 2011;Facio et al 2013;Haga et al 2011;Haga et al 2012;Savage Bennette et al 2013;Townsend et al 2012), is that participants were asked about hypothetical, rather than actual, choices. Also, only about one third of patients invited to the study opted into the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that initial strong interest in genetic testing does not always translate into actual uptake of testing Meiser and Dunn 2000); thus the major weakness of this study, shared with almost all studies published in this area (Biesecker et al 2009;Bloss et al 2010;Facio et al 2011;Facio et al 2013;Haga et al 2011;Haga et al 2012;Savage Bennette et al 2013;Townsend et al 2012), is that participants were asked about hypothetical, rather than actual, choices. Also, only about one third of patients invited to the study opted into the study.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the available studies address preferences of the lay public (e.g., Bloss et al 2010;Haga et al 2011;Haga et al 2012), and research participants (e.g., Biesecker et al 2009;Facio et al 2011;Facio et al 2013), regarding the returning of results, as opposed to patients undergoing diagnostic testing. However, very recent research efforts have also started to examine patient perspectives of genomic testing (Miller et al 2014;Savage Bennette et al 2013;Shahmirzadi et al 2013;Townsend et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Guidelines have become available for a number of medications with applicable PGx testing through the Clinical Pharmacogenetics Implementation Consortium [7][8][9]. Although physicians may perceive a benefit to using PGx [3,5,[9][10][11][12], many barriers exist that have prevented implementation on a larger scale such as: physicians lacking sufficient knowledge and finding time to keep up-to-date; uncertainty surrounding clinical utility; lack of confidence or comfort in ordering PGx testing; lack of comfort interpreting results; uncertainty in how to communicate results to patients and having sufficient time to do so; difficulty in managing changes to workflow; determining how to incorporate results into the electronic medical record (EMR); and uncertainty about level of coverage by insurance and reimbursement [3,5,6,[9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…General ethical concerns regarding pharmacogenetic testing were raised in the studies by Haga et al who assessed attitudes toward pharmacogenetic testing in the general public and in various focus groups (healthcare professionals, primary care professionals and geneticists) (159,160). In the focus groups, they found that the overall attitude was generally positive, but a few concerns were raised in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…These included clinical utility, insurance coverage, treatment delay, and the communication of ancillary disease information as principal concerns (161). Those studies concluded that additional educational resources, access to genetic counseling, improved clinical guidelines and cost-benefit analyses are warranted prior to large-scale implementation (159,160).…”
Section: Discussionmentioning
confidence: 99%